Synthesis and Characterization of Chitosan-Coated Near-Infrared (NIR) Layered Double Hydroxide-Indocyanine Green Nanocomposites for Potential Applications in Photodynamic Therapy - Wei, Pei-Ru (Int J Mol Sci, 2015)
We designed a study for photodynamic therapy (PDT) using chitosan coated Mg–Al layered double hydroxide (LDH) nanoparticles as the delivery system. A Food and Drug Administration (FDA) approved near-infrared (NIR) fluorescent dye, indocyanine green (ICG) with photoactive properties was intercalated into amine modified LDH interlayers by ion-exchange. The efficient positively charged polymer (chitosan (CS)) coating was achieved by the cross linkage using surface amine groups modified on the LDH nanoparticle surface with glutaraldehyde as a spacer. The unique hybridization of organic-inorganic nanocomposites rendered more effective and successful photodynamic therapy due to the photosensitizer stabilization in the interlayer of LDH, which prevents the leaching and metabolization of the photosensitizer in the physiological conditions. The results indicated that the polymer coating and the number of polymer coats have a significant impact on the photo-toxicity of the nano-composites. The double layer chitosan coated LDH–NH(2)–ICG nanoparticles exhibited enhanced photo therapeutic effect compared with uncoated LDH–NH(2)–ICG and single layer chitosan-coated LDH–NH(2)–ICG due to the enhanced protection to photosensitizers against photo and thermal degradations. This new class of organic-inorganic hybrid nanocomposites can potentially serve as a platform for future non-invasive cancer diagnosis and therapy.